The Implementation of audio - visual aids to teach english Communicatively to senior high school semi - distance english students from educame program at caes. - Herrera Barrientos, Azalea Maribel; Molina Martinez, Juan Antonio; Peraza Peraza, Ana Edith (2024)
The inportance of english -- Educame -- Educame modalities -- Speaking and listening skills -- Integration of oral and listening skills.